New Languages of the State : Indigenous Resurgence and the Politics of Knowledge in Bolivia - Gustafson, Bret Darin, 1968- (Book collections on Project MUSE., 2009)
Analyzes bilingual intercultural education in Bolivia to show how indigenous-backed proposals to reform the all-Spanish education system to include indigenous languages and knowledges challenged neoliberal models of education and became part of the transf.